Exploring factors influencing outcomes of a five-week youth expedition in the Himalayas using the sail training programme self-assessment toolkit - Tim Scott; Pete Allison; Kris von Wald; Omolabake Fakunle (Karolinum Press, 2016)
Much evidence to link youth expeditions and gap years with a range of outcome benefits for participants exists, but to date, there have been relatively few insights into what exactly brings about these reported outcomes. A modified version of the Sail Training Voyage Toolkit (2011) was used to evaluate outcomes of a five-week British Exploring Society youth expedition in the Himalayas. Data generated from 22 participants completing the modified Sail Training Voyage Feedback Form at the end of their expedition were complemented by data from 16 interviews conducted during weeks one, three and five of the expedition. Key factors identified by the participants which had influenced their learning were: (1) Other Young Explorers, (2) being involved in making decisions and having choices, (3) having time to learn at their own pace; time to get comfortable with people; being able to talk with other people (to make connections); (4) group leaders, and (5) wild camping. Data from 16 interviews supported these outcomes, while the physical challenges (of climbing peaks) and cultural interaction with local people were highly valued aspects of the expedition. Participants were more aware of risks and more confident about safety issues and taking risks after the expedition. These important outcomes may be transferred to future expeditions, higher education or employment. Personal development and training organisations should consider these findings.